(untitled) (International Journal of Innovative Computing, 2021)
A mangrove vulnerability assessment’s goal is to generate recommendations for reducing vulnerability. Mangrove forests, which grow in the intertidal zones and estuary mouths between land and sea, exist in two worlds at once. Mangroves provide crucial stability for preventing shoreline erosion. It helps to maintain land level by sediment accretion while balancing sediment loss by serving as buffers catching materials washed downstream. Climate change, especially the associated increase in sea level, poses a serious threat to mangrove coastal areas, and it is critical to devise strategies to mitigate vulnerability through strategic management planning. Experts are attempting to determine how mangroves have been affected by climate change and rising sea levels. How do we forecast the consequences and effect of rising sea levels on mangroves, and then adjust and mitigate them accordingly? Vulnerability implies the risk of being assaulted or hurt, whether physically or emotionally. Environmental vulnerability is a feature of impact exposure as well as ecological systems’ susceptibility and adaptive potential to environmental tensors. Researchers in this study ranked mangrove vulnerability on a scale of 1 to 5, with 1 indicating very low vulnerability and 5 indicating very high vulnerability. The Physical Mangrove Index (PMI), Biological Mangrove Index (BMI), and Threat Mangrove Index (HMI) are the three major groups of the Mangrove Vulnerability Index (MVI)). The study’s main objective is to develop an accurate and efficient GIS database system that has been formulated and tested or implemented in three (3) separate areas, namely, Kukup Island, Tanjung Piai, and Sungai Pulai. The study develops a GIS-based Mangrove Vulnerability Index (MVI) Model for a selected ecosystem, and highlights mangrove vulnerability by ranking them from least to most vulnerable using parameters. The study also provides a forecast for the mangrove loss in the next 50 and 100 years, as well as to classify areas where mangroves are most vulnerable.